In situ biosynthesis of palladium nanoparticles on Artemisia abrotanum extract-modified graphene oxide and its catalytic activity for Suzuki coupling reactions. (1st June 2019) - Salehi, Mirmehdi Hashemi; Yousefi, Mohammad; Hekmati, Malak; Balali, Ebrahim
Graphical abstract: A new and effective reusable Pd catalyst supported on Artemisia abrotanum extract-modified GO was suggested for the Suzuki coupling reactions. Abstract: We progressed the catalytic activity of Pd NPs coated on Artemisia abrotanum extract-modified graphene (Pd NPs/RGO) for the Suzuki coupling reactions. Pd NPs/RGO nanocatalyst was fabricated via modifying the surface of graphene oxide (GO) with A. abrotanum extract as a reducing and stabilizing agent with no addition of any toxic agent to in situ reduction and immobilizing Pd nanoparticles. Sundry methods like FTIR, UV–Vis, ICP-AES, XRD, FE-SEM, WDX, TEM and EDX have been used for explaining the structure and morphology of the Pd NPs/RGO nanocatalyst. The outcomes indicate that the Pd (0) nanoparticles are completely spread on the functionalized GO surface. Pd NPs/RGO showed excellent catalytic performance as a recyclable nanocatalyst in Suzuki-Miyaura reactions with high yields. Moreover, the recycled nanocatalyst showed no considerable loss in its activity.